Intensity-modulated radiotherapy versus three-dimensional conformal radiotherapy during deep inspiratory breath hold for left-sided whole-breast irradiation: a comparative analysis. Issue 1 (7th September 2015) - Trifiletti, D. M.; Wijesooriya, K.; Moyer, G.; Lain, D.; Geesey, C.; Forbes, K.; Reardon, K. A.
Abstract: Aim: Deep inspiratory breath hold (DIBH) during left-breast irradiation helps to minimise cardiac irradiation by physically separating the heart from the left breast. The dose to organs-at-risk in intensity-modulated radiotherapy (IMRT) and opposed tangent three-dimensional conformal radiotherapy (3DCRT) during DIBH in patients with left-sided breast cancer was compared. Materials and methods: A total of 20 consecutive patients with left-sided breast cancer had a computed tomography scan utilising DIBH. Mean volumes of the heart, left anterior descending coronary artery, total lung and right breast receiving 5–95% of the prescription dose were calculated. Results: Target volume homogeneity was improved with IMRT and average mean dose to target was higher for 3DCRT (51·03 Gy) compared with IMRT (50·47 Gy, p <0·01). The average mean dose to the heart was lower with 3DCRT (87 versus 77 cGy, p <0·01). The average mean dose to the contralateral breast was also lower with 3DCRT (19 versus 17 cGy, p <0·01). Less monitor units (MUs) were required with 3DCRT with an average difference of 225 MU/fraction ( p <0·01). Findings: Under DIBH, absolute differences between 3DCRT and IMRT were minimal. 3DCRT under DIBH provided excellent dosimetric results in most patients with left-sided breast cancer without the need for IMRT.